Digital Stories and Inclusive Cultures at School: A Research Study in an Italian Primary Multicultural Classroom - Flavio Manganello; Mara Baldacci (MDPI AG, 2024)
This study explores the effectiveness of digital storytelling in enhancing communicative competence-encompassing both linguistic and narrative skills-and fostering inclusivity in a multicultural primary classroom in Genoa, Italy. The quasi-experimental intervention spanned four months and involved eight lessons designed to engage students from diverse cultural backgrounds, particularly those with migratory backgrounds. Pre- and post-intervention assessments were conducted to evaluate linguistic proficiency, narrative competence, and educational inclusion. The results from the Italian language proficiency test demonstrated that second-generation students typically performed at the B1 level, while students with more recent migratory backgrounds scored lower. However, narrative competence showed notable improvements among A2+ level students, who outperformed their peers in certain dimensions despite linguistic challenges. Observational rubrics used throughout the intervention revealed increased classroom inclusivity, active participation, and cultural exchange. Despite limitations related to the sample size and intervention duration, the findings suggest that digital storytelling can significantly enhance communicative competence and promote a more inclusive classroom environment. Future research should investigate the long-term effects of digital storytelling on multilingual classrooms and its broader applicability.